Usability evaluation study of the interface of a guided diagnosis robot based on eye movement experiments - Dou, Shilin; Du, Hemin; Xu, Fei; Hong, Ruiye (Proceedings of SPIE, the international society for optical engineering, 2025)
This study aims to enhance the usability and operational efficiency of the diagnosis-guiding robot interface at Union Hospital, Huazhong University of Science and Technology, Shenzhen, China, through an analysis of interaction design using eye movement experiment results. A subjective-objective usability evaluation method was employed to assess the XiaoYi interface. The Tobii Pro Glasses2 eye-tracking test was conducted on 31 subjects, focusing on the “pre-examination and triage” and “departmental specialist view” functions. The study concludes that eye movement experiments, combined with quantitative and qualitative analyses, can effectively guide improvements in the diagnosis of robot interfaces, evaluate system ease of learning and cognitive load, and validate the feasibility of this method in interface optimization and evaluation.